2016
DOI: 10.2147/ijn.s101251
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic core shell nanoparticles containing dense polyethyleneimine shells for efficient delivery of microRNA to Kupffer cells

Abstract: Efficient and targeted delivery approach to transfer exogenous genes into macrophages is still a great challenge. Current gene delivery methods often result in low cellular uptake efficiency in vivo in some types of cells, especially for the Kupffer cells (KCs). In this article, we demonstrate that amphiphilic core–shell nanoparticles (NPs) consisting of well-defined hydrophobic poly(methyl methacrylate) (PMMA) cores and branched polyethyleneimine (PEI) shells (denoted as PEI@PMMA NPs) are efficient nanocarrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The utilisation of polymer-based nanoparticles for enabling the delivery of a spectrum of drugs, including miRNAs, is becoming evermore commonplace with versatile and non-immunogenic polymers such as polyethylenimine and polyethylene glycol being utilised as nanoparticle backbones [121][122][123][124][125]. Typical advantages of the use of polymers for nanoparticle drug delivery systems include a highly flexible drug release kinetic profile on response to acid exposure [93].…”
Section: Non-viral-based Delivery Systems (A) Polymer Nanoparticlesmentioning
confidence: 99%
“…The utilisation of polymer-based nanoparticles for enabling the delivery of a spectrum of drugs, including miRNAs, is becoming evermore commonplace with versatile and non-immunogenic polymers such as polyethylenimine and polyethylene glycol being utilised as nanoparticle backbones [121][122][123][124][125]. Typical advantages of the use of polymers for nanoparticle drug delivery systems include a highly flexible drug release kinetic profile on response to acid exposure [93].…”
Section: Non-viral-based Delivery Systems (A) Polymer Nanoparticlesmentioning
confidence: 99%
“…Several substances such as chitosan [83], PEI (polyethyleneimine) nanoparticles [84], 15% of N-acetyl cysteine (NAC) [87], calcium phosphate cement (CPC) [90], acrylic resin of different colors [91], (bone cement) enriched with microencapsulated 2-octyl cyanoacrylate (OCA), extracts solutions [92], scaffolds fabricated by electrospinning using polycaprolactone (PCL) [94], core/polyethyleneimine (PEI) shell magnetic nanoparticles [97], silver nanoparticles (AgNPs) [98], and Paladon 65-HR precoated with biosurfactant were also evaluated for cytotoxicity. The authors observed reduction in cytotoxicity and increase in biocompatibility from non-cytotoxic (cell viability higher than 75%) to slightly cytotoxic (cell viability ranging from 50 to 75%)…”
Section: Short-or Long-term Injection or Implantation Studiesmentioning
confidence: 99%